Les communautés d'apprenants en réseau au bénéfice de l'éducation - Laferrière, Thérèse (2005)
The contribution of information and communication technologies to pedagogical innovation is understood from the cognitive and social perspectives on learning. The notion of networked communities is put forward and three application models are presented: the classroom-based learning community, the community of practice, and the knowledge building community. These three models are illustrated: context, participants, cultural artifacts, and digital tools. These emerging models and related social technical designs are in the reach of those willing to use the Internet for their own learning and for helping others to learn in a collaborative manner.